(untitled) (Gilgameš, 2016)
This paper deals with Claudian’s epic-historical poem Bellum Geticum, where the author praises Stilicho’s achievements during Geticum, where the author praises Stilicho’s achievements during Alaric’s invasion of Italy (401 A.D.). The essay starts with a brief exposition of the historical events, and then proceedes with a critical investigation on Claudian’s attempts to transfigure them in a more acceptable reality for his audience. Roman past is idealised; the half- barbarian Stilicho unifies in his person all the military and tactical skills of Rome’s greatest generals; Alaric is portrayed both as a fierce barbarian dressed in pelts and as a new Hannibal; lastly, Stilicho’s little success on Alaric in the battle of Pollentia is celebrated as the final and conclusive revenge of the imperial army for the defeat suffered by the hands of the Goths at Adrianople in 378 A.D.